Patterns in Vegetables Consumption in Kashmir Valley, India - Akhter, Saima; Bhat, Mohammad Shafi; Bhat, Showkat Anwar (International Journal of Agriculture System, 2024)
Over the years, the consumption of vegetables has grown. Due to growing consumer concern over health-related issues, this has happened. The purpose of this study is to investigate the patterns in vegetable consumption and exploration of the underlying factors for that existing pattern. In this study, information was gathered from household surveys. Data was analyzed using multinomial logistic regression and descriptive analysis. The majority (76.6%) of the respondents had up to seven family members. one-third of the sampled population falls in the service sector of the economy (43%). most of the sample households were from rural backgrounds (55.9%). Around (87.8%) of the sample population consumed less than 3 servings of vegetables in a day.  The quantity of vegetable consumption as a dependent variable has three categories less than, greater than, and equal to three serving sizes. While taking greater than three serving sizes as a reference category and less than three serving sizes as the dependent variable. It was found that as the family size increases from three members to more than that there is a likelihood increase in taking vegetables more on a per capita basis per day with an odds ratio of 0.21(0.4-0.9), similarly there is a likelihood increase in the vegetable consumption with the increase in monthly income 0.5(0.12-0.95), as the frequency of buying vegetables increases there is an increase in vegetable consumption, accessibility has also significant bearing on its intake. Due to less access to the marketplaces, rural residents have low trips to grocery shops and rely mostly on homegrown vegetables. Respondents from urban residents have frequent trips to the grocery shops mostly due to the availability of vegetables. The results show that implementing an appropriate pricing strategy and promoting market infrastructure will augment the dietary diversity in the population which will lead to the holistic development of the vegetable industry as well as the required nutritional needs efficiently.